2018
DOI: 10.1016/j.amepre.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Sexual Orientation in a National Cross-sectional Study: Age, Race/Ethnicity, and Sexual Identity–Attraction Differences

Abstract: These findings provide valuable new information about sexual minority subgroups, such as self-identified bisexual older adults and sexual identity-attraction discordant women, that appear to be at higher risk for adverse smoking-related health consequences as a result of their elevated rates of cigarette smoking. Additional attention is warranted to examine these high-risk subpopulations prospectively and, if the results are replicated with larger samples, this information can be used to target smoking-cessati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 35 publications
(54 reference statements)
9
51
0
Order By: Relevance
“…Although the underlying argument for this approach is grounded in theoretical and empirical understandings of SM health inequities, 22,23 we illustrate the utility of this approach using nationally representative data that have been used to provide some of the more prominent findings regarding sexual orientation disparities in mental health and substance abuse. 8,10,[17][18][19] Similar to previous research, 3,4,8,10 our findings from unconditional models-models that do not adjust for sexual identity-showed different patterns of mental health and substance use disorders risk, across measures of sexual orientation, for both men and women. However, findings from conditional models-models adjusted for sexual identity-demonstrate the degree to which sexual identity plays both a unique and overlapping role in the relationship between sexual attraction/behavior and health, particularly among men.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although the underlying argument for this approach is grounded in theoretical and empirical understandings of SM health inequities, 22,23 we illustrate the utility of this approach using nationally representative data that have been used to provide some of the more prominent findings regarding sexual orientation disparities in mental health and substance abuse. 8,10,[17][18][19] Similar to previous research, 3,4,8,10 our findings from unconditional models-models that do not adjust for sexual identity-showed different patterns of mental health and substance use disorders risk, across measures of sexual orientation, for both men and women. However, findings from conditional models-models adjusted for sexual identity-demonstrate the degree to which sexual identity plays both a unique and overlapping role in the relationship between sexual attraction/behavior and health, particularly among men.…”
Section: Discussionsupporting
confidence: 85%
“…[13][14][15][16], * As such, models that do not adjust for sexual identity when estimating associations between attraction and/or behavior and any given health outcome do not properly estimate health risk for heterosexual-identified SM people; for example, those with a heterosexual identity but same-sex attraction and/or same-sex behavior, the combination of which influences their day-to-day experiences, behaviors, and subsequently health. [15][16][17][18][19] In other words, not accounting for the unique and shared variance of sexual identity alongside other measures of sexual orientation obscures health differences across measures of attraction and behavior independent of that sexual identity. These two interrelated issues demonstrate how the approach to independently estimating sexual orientation differences in health risk across discrete measures of sexual orientation lacks specificity and limits the utility of the results drawn from this approach to make strong inferences about differential risk based on sexual identity, attraction, and behavior.…”
Section: Estimating Health Disparities Across Multiple Measures Of Sementioning
confidence: 99%
See 1 more Smart Citation
“…46 No racial/ethnic differences in health behaviors were identified. With a few exceptions, 55 there is a paucity of research examining racial/ ethnic differences in psychosocial and behavioral risk factors for CVD in SMW. 6 Future studies should use intersectional approaches to examine which subgroups of SMW are most at risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…However, SUD are not homogeneous among SM populations, and differences exist between male and female SM [3]. Although TUD is higher among all SM adults compared to heterosexual adults [5,6], SM women are more likely than SM men to use tobacco products [7,8]. Studies also have found AUD to be significantly higher among SM individuals [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%